Integrating interprofessional electronic medical record teaching in preregistration healthcare degrees: A case study. (January 2023) - Lokmic-Tomkins, Zerina; Gray, Kathleen; Cheshire, Lisa; Parolini, Arno; Sharp, Megan; Tarrant, Bronwyn; Hill, Nicole; Rose, David; Webster, Marilyn; Virtue, Debra; Brignell, Amanda; Waring, Rebecca; et al.
Abstract: Background: Electronic medical record (EMR) adoption across healthcare necessitates a purposeful curriculum design to prepare graduates for the delivery of safe and effective patient care in digitally-enabled environments. Objective: To describe the design and development of an Interprofessional Electronic Medical Record (iEMR) subject that introduces healthcare students to its utility in clinical settings. Methods: A six-stage design-based educational research framework (Focus, Formulation, Contextualisation, Definition, Implementation, Evaluation) was used to instigate the iEMR design and development in nursing and five allied health graduate entry to practice (preregistration) degrees at an Australian university. Results: In the Focus process, the concept and interdisciplinary partnerships were developed. The Formulation process secured grant support for subject design and development, including a rapid literature review to accommodate various course and curriculum structures. Discipline-specific subject themes were created through the Contextualisation process. During the Definition process, learning objectives and content resources were built. The Implementation process describes the pilot implementation in the nursing program, where assessment tasks were refined, and interdisciplinary clinical case studies originated. Discussion: The design and development of an iEMR subject is underpinned by internal support for educational innovation and in alignment with digital health strategies in employer organisations. Identified barriers include faculty-level changes in strategic support for teaching innovation, managerial expectations of workload, the scope of work required by academics and learning designers, and the gap between the technology platform required to support online learning and the infrastructure needed to support simulated EMR use. A key discovery was the difficulty of finding EMR software, whether designed for teaching purposes or for clinical use, that could be adapted to meet the needs of this project. Conclusion: The lessons learned are relevant to educators and learning designers attempting a similar process. Issues remain surrounding the sustainability of the iEMR subject and maintaining academic responsibility for ongoing curriculum management.